Research on the Learning Interest of Graduate Students Majoring in Mathematics - Yang, Zezhong; Shi, Chunge (American Journal of Creative Education, 2020)
Mathematics plays an irreplaceable role in all fields of society with its strong foundation. It is of great significance to strengthen mathematics education, especially for graduate students. However, according to the current learning state of mathematics graduate students, their enthusiasm for scientific research is not high. Therefore, this study takes all the master degree students of mathematics major in 2019 from the school of mathematics and statistics of Shandong Normal University as the objects of investigation, and issues questionnaires to the students, and uses the method of quantitative analysis to study the current situation of mathematics learning interest of the graduate students of mathematics major. The results show that the graduate students majoring in mathematics are interested in mathematics learning in the mass, but the degree of interest is not high, although these students are active in taking notes on mathematics. Therefore, in daily teaching, graduate tutors should pay closer attention to lead and develop students’ studying interest to improve their learning motivation.